The Influence of Price Strategy in the Marketing Mix on Costumer Purchasing Decisions at Indocellular Tulungagung - sholeh, Muh Ibnu; Sokip; Asrop Syafi’i; Dwi andayani; Sahri (MultiTech Publisher, 2023)
This research aims to determine the relationship between price, quality, promotion and service strategies in the marketing mix and consumer purchasing decisions at Indocellular Tulungagung. This research is an explanatory type. The population is all Indocellular employees, totaling 35 people. The research sample is saturated sample which also consists of 35 people. The data collection method was carried through distributing questionnaires directly to respondents. Data analysis uses Structural Equation Modeling (SEM) techniques based on the Partial Least Squares (PLS) variant. SEM testing is carried out with the Smart PLS application, including testing the Measurement Model (Outer Model), Structural Model (Inner Model), and Hypothesis Testing. The research results show that there is positive and significant influence between Price, Quality, Promotion and Service Strategy in the marketing mix on consumer purchasing decisions at Indocellular Tulungagung. Price Strategy has a significant influence on Purchasing Decisions (regression coefficient 0.65, T-value 7.42, P-value 0.001), as well Quality (regression coefficient 0.50, T-value 5.21, P-value 0.005), Promotion (regression coefficient 0.30 , T-value 3.14, P-value 0.025), and Service (regression coefficient 0.40, T-value 4.12, P-value 0.01). The overall results support the four research hypotheses, confirming that the aspects in the marketing mix together contribute significantly to consumer purchasing decisions